Valued experiences of graduate students in their role as educators in undergraduate training in Ugandan medical schools. Issue 1 (December 2017) - Rukundo, Godfrey; Kasozi, Jannat; Burani, Aluonzi; Byona, Wycliff; Kirimuhuzya, Claude; Kiguli, Sarah
Abstract Background In most medical schools, graduate students, sometimes referred to as graduate teaching assistants, often participate in the training of undergraduate students. In developing countries like Uganda, are typically involved in undergraduate training. However, prior to this study there were no standard guidelines for this involvement. At the same time, the views and experiences of the graduate students in their role as educators had not been documented. Therefore, the aim of this study was to explore the views and experiences of graduate students about their involvement in undergraduate training in three Ugandan medical schools. The findings of this study will contribute to the development of policies for training in Ugandan medical schools. Methods This was a qualitative study in which thirty in-depth-interviews were conducted among second and third year graduate students in three Ugandan medical schools in the MESAU consortium (Medical Education Services to all Ugandans) including Mbarara University of Science and Technology, Makerere College of Health Sciences and Kampala International University, Western Campus. Results All graduate students from all the three medical schools viewed their involvement in undergraduate training as important. The study also revealed that graduate students increase available human resources and often compensate for the teaching missed when senior educators were absent. The graduate students expressed important views that need to be considered in the design of educational programs where they are to be involved. The respondents also reported a number of challenges in this undertaking that included lack of motivation, lack of orientation and having heavy workloads. The presence and commitment of senior educators to guide and support the graduate students in teaching activities was viewed as one significant intervention that would increase the effectiveness of their educational contributions. Conclusions Graduate students enjoy their involvement in the training of undergraduate students despite the various challenges they face. In some departments, the involvement of postgraduate trainees is critical to the viability of undergraduate medical training.